An introduction to differential equations and their applications - Farlow, Stanley J., 1937- (Dover Publications, 2006)
Starting with an introduction to differential equations, this insightful text then explores 1st- and 2nd-order differential equations, series solutions, the Laplace transform, systems of differential equations, difference equations, nonlinear differential equations and chaos, and partial differential equations. Numerous figures, problems with solutions, and notes. 1994 edition. Includes 268 figures and 23 tables.